Improving capacity to care for patients with intellectual and developmental disabilities: The value of an experiential learning model for family medicine residents. Issue 3 (July 2022) - Selick, Avra; Durbin, Janet; Casson, Ian; Green, Laurie; Abells, Dara; Bruni, Alison; Mazurek, Matthew T.; Jiwa, Muhammad Irfan; Lunsky, Yona
Abstract: Background: Patients with intellectual and developmental disabilities (IDD) are more likely to experience poor health outcomes and family physicians receive inadequate training to provide appropriate care to this patient group. Little prior research has studied how to effectively train family physicians to care for patients with IDD. Objective: The aim of this pilot study was to assess the value of adding an experiential component to didactic education strategies to improve family medicine resident perceived comfort, skills and knowledge related to caring for patients with IDD. Methods: Structured education programs for residents were implemented at three primary care practices in Ontario, Canada. Two practices received didactic information only (didactic-only group); one received didactic information and an experiential training model including clinical interactions and a written reflection on that experience (didactic plus experiential group). In this separate-sample pre-post design, residents were invited to complete a brief anonymous survey prior to and following the training assessing their perceived comfort, skills and knowledge related to patients with IDD. Results: At baseline, there were no significant differences between the two groups of residents. At follow up, the experiential group reported significantly higher levels of comfort, skills, and knowledge compared to baseline for most items assessed, while in the didactic-only group most items showed little or no improvement. Conclusion: This pilot study suggests that providing residents the opportunity to participate in clinical encounters with patients with IDD, as well as a structured process to reflect on such encounters, results in greater benefit than didactic training alone.